Odpowiedzi

Najlepsza Odpowiedź!
2009-11-09T12:09:19+01:00
W(x)=-x³+2x²-3x+a
W(1)=4
a) W(1)= -1+2-3+a=4
-2+a=4
a=6
W(x)=-x³+2x²-3x+6
b)W(x)=-x³+2x²-3x+6
W(x)= -x²(x-2)-3(x-2)= (x-2)(-x²-3)=-(x-2)(x²+3)
c)W(x)=-x³+2x²-3x+6=0
Korzystamy z podpunktu b
-(x-2)(x²+3)=0
x=2 x²=-3-sprzeczność
Zatem wielomian ma jeden pierwiastek x=2
1 5 1
2009-11-09T12:11:20+01:00
W(x)=-x³+2x²-3x+a

a)W(1) = 4
4 = -1³+2 * 1²-3 * 1+a
4 = -1 + 2 - 3 + a
4 = -2 + a
a = 6

b)
W(x) = -x³+2x²-3x+6
W(x) = x² * (-x + 2) + 3 * (-x + 2)
W(x) = (-x + 2) * (x² + 3)
W(x) = -(x - 2) * (x² + 3)

c) W(x) = 0
x - 2 = 0 lub x² + 3 = 0
x = 2


2009-11-09T13:19:06+01:00
A)
(-1³) +2*1²-3*1+a=4
-1+2-3+a=4
-2+a=4
a=6
b) W(x)=-x³+2x²-3x+6
W(x)=-x³+2x²-3x+6
W(x)= -x²(x-2)-3(x-2)= (x-2)(-x²-3)=-(x-2)(x²+3)


c)-x³+2x²-3x+a=0
-(x-2)(x²+3)=0
-(x-2)=0 ∨ x²+3=0
-x+2=0 ∨ x²=-3 (sprzeczne)

x=2 ∨ x²=-3 (sprzeczne)